Keteladanan Guru Mata Pelajaran Adab dalam Penguatan Karakter Religius Santriwati Madrasah Aliyah Tahfizh Nurul Iman Karanganyar - Suyatman, Suyatman; Subando, Joko; Sukari, Sukari (TSAQOFAH, 2026)
The formation of religious and disciplined character is a primary goal of Islamic education, particularly in pesantren-based institutions, thereby requiring effective learning methods for the internalization of these values. This study aimed to describe the implementation of a teacher role-model-based learning method in adab lessons to strengthen the religious and disciplinary character of female students at MA Tahfizh Nurul Iman Karanganyar. The research employed a qualitative approach with a descriptive design, with data collected through observation, interviews, and documentation. The findings show that the implementation of teacher role modeling is manifested through teachers’ religious behavior, discipline in time management, exemplary speech, and consistency of attitude in daily teaching and learning activities. The role-modeling method proved effective in continuously strengthening the religious and disciplinary character of students, as they tend to imitate the attitudes and behaviors of teachers perceived as role models. The main supporting factor is the pesantren environment, which is conducive to the habituation of religious and disciplinary values, while the inhibiting factor lies in the diverse backgrounds of students, which influence their readiness and responses to value internalization. The study concludes that teacher role-model-based learning is a key strategy for reinforcing the religious and disciplinary character of students and offers practical implications for the development of learning practices in pesantren-based Islamic educational institutions.